A TEN YEAR STUDY OF POISONING CASES IN A TERTIARY CARE HOSPITAL (Indian Internet Journal of Forensic Medicine and Toxicology, 2004)
A 10 years' autopsy study (1994-2003) of deaths due to poisoning was carried out in the department of Forensic Medicine & Toxicology, GMCH Chandigarh. The objective of the study was to ascertain the various aspects of deaths due to poisoning and to find remedial measures to decrease the incidence of poisoning cases. The incidence of deaths due to poisoning was found to be persistently increasing. Maximum number of cases (49.07%) were observed in adolescents and young adults (age group: 15-25  years). Male-female ratio was 2.8: 1. Rural- urban ratio was 1.62:1.Among the male victims married outnumbered unmarried in rural population, while in urban population reverse was observed. Among the females married outnumbered unmarried in both rural and urban population. Aluminium phosphide (ALP) was found to be the 'Poison of choice for suicides and suicide was the most common (93.09%) mode of poisoning. Based on the conclusions of the study various suggestions have been put forward to decrease the incidence of poisoning.
Keywords: measures; poison